If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(x + 2) + -3(4x + -3) = (x + -5) * 2 Reorder the terms: (5 + x)(x + 2) + -3(4x + -3) = (x + -5) * 2 Reorder the terms: (5 + x)(2 + x) + -3(4x + -3) = (x + -5) * 2 Multiply (5 + x) * (2 + x) (5(2 + x) + x(2 + x)) + -3(4x + -3) = (x + -5) * 2 ((2 * 5 + x * 5) + x(2 + x)) + -3(4x + -3) = (x + -5) * 2 ((10 + 5x) + x(2 + x)) + -3(4x + -3) = (x + -5) * 2 (10 + 5x + (2 * x + x * x)) + -3(4x + -3) = (x + -5) * 2 (10 + 5x + (2x + x2)) + -3(4x + -3) = (x + -5) * 2 Combine like terms: 5x + 2x = 7x (10 + 7x + x2) + -3(4x + -3) = (x + -5) * 2 Reorder the terms: 10 + 7x + x2 + -3(-3 + 4x) = (x + -5) * 2 10 + 7x + x2 + (-3 * -3 + 4x * -3) = (x + -5) * 2 10 + 7x + x2 + (9 + -12x) = (x + -5) * 2 Reorder the terms: 10 + 9 + 7x + -12x + x2 = (x + -5) * 2 Combine like terms: 10 + 9 = 19 19 + 7x + -12x + x2 = (x + -5) * 2 Combine like terms: 7x + -12x = -5x 19 + -5x + x2 = (x + -5) * 2 Reorder the terms: 19 + -5x + x2 = (-5 + x) * 2 Reorder the terms for easier multiplication: 19 + -5x + x2 = 2(-5 + x) 19 + -5x + x2 = (-5 * 2 + x * 2) 19 + -5x + x2 = (-10 + 2x) Solving 19 + -5x + x2 = -10 + 2x Solving for variable 'x'. Reorder the terms: 19 + 10 + -5x + -2x + x2 = -10 + 2x + 10 + -2x Combine like terms: 19 + 10 = 29 29 + -5x + -2x + x2 = -10 + 2x + 10 + -2x Combine like terms: -5x + -2x = -7x 29 + -7x + x2 = -10 + 2x + 10 + -2x Reorder the terms: 29 + -7x + x2 = -10 + 10 + 2x + -2x Combine like terms: -10 + 10 = 0 29 + -7x + x2 = 0 + 2x + -2x 29 + -7x + x2 = 2x + -2x Combine like terms: 2x + -2x = 0 29 + -7x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-29' to each side of the equation. 29 + -7x + -29 + x2 = 0 + -29 Reorder the terms: 29 + -29 + -7x + x2 = 0 + -29 Combine like terms: 29 + -29 = 0 0 + -7x + x2 = 0 + -29 -7x + x2 = 0 + -29 Combine like terms: 0 + -29 = -29 -7x + x2 = -29 The x term is -7x. Take half its coefficient (-3.5). Square it (12.25) and add it to both sides. Add '12.25' to each side of the equation. -7x + 12.25 + x2 = -29 + 12.25 Reorder the terms: 12.25 + -7x + x2 = -29 + 12.25 Combine like terms: -29 + 12.25 = -16.75 12.25 + -7x + x2 = -16.75 Factor a perfect square on the left side: (x + -3.5)(x + -3.5) = -16.75 Can't calculate square root of the right side. The solution to this equation could not be determined.
| -6x-3x=9 | | 3x-45=26 | | (5y-2)-(3y+8)= | | X+1+1=5 | | -1/8(x-3/8)=-1/9(x-3/8) | | 3.25x=-39 | | 6(y+9)+y=4(y+4)-2 | | 9x^2+4x-4=3x^2 | | 1-2x+3=12 | | 2v-16=2 | | 8.25y=-115.5 | | 1-5x-6x=-10 | | 36-1/26(4x)=27-1/26(3x) | | 4x-7=2x-4 | | x+iy=4-2i | | y^2+19y+84= | | 7(1-2x)=-6x-33 | | 62=8n-2 | | 2(x+1)=x-9 | | 8x-7w+4x+8y+3y+5w= | | -x-17=-4x+1 | | c+18=50 | | -6=2z+14 | | 4x-1+2x=5x+4x | | 1.16x=5.80 | | -y+7=2y+7 | | 35-3v=2v+5 | | 8x+2(-5-3x)=8-7x | | 0=7w-34 | | 6y-42=5y+20 | | b-14=28 | | 6n^2+18n=0 |